2017
DOI: 10.1096/fj.201700056r
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A is required for spindle migration and asymmetric division in mouse oocytes

Abstract: Dynamic changes in the actin network are crucial for the cortical migration of spindles and establishment of polarity, to ensure asymmetric division during meiotic maturation. In this study, filamin A (FLNA) was found to be an essential actin regulator that controlled spindle migration and asymmetric division during oocyte meiosis. FLNA was localized in the cytoplasm and enriched at the cortex and near the chromosomes. Knockdown of FLNA impaired meiotic asymmetric division and spindle migration with a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Expectedly, our data illustrated that DDP exposure decreased the acetylation level of α-tubulin, indicating that the loss of microtubule stability might be one of the major causes leading to the disorganized spindle structure. Additionally, the dynamics of actin filament, another indispensable component of cytoskeleton, has been reported to play important roles in spindle positioning and meiotic progression during oocyte meiosis [4648]. Our findings validated that the perturbed actin polymerization might be another major reason resulting in the oocyte meiotic failure when exposed to DDP.…”
Section: Discussionsupporting
confidence: 79%
“…Expectedly, our data illustrated that DDP exposure decreased the acetylation level of α-tubulin, indicating that the loss of microtubule stability might be one of the major causes leading to the disorganized spindle structure. Additionally, the dynamics of actin filament, another indispensable component of cytoskeleton, has been reported to play important roles in spindle positioning and meiotic progression during oocyte meiosis [4648]. Our findings validated that the perturbed actin polymerization might be another major reason resulting in the oocyte meiotic failure when exposed to DDP.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, TUBA1 increased with oocyte diameter, and CFLN increased with oocyte maturation and cumulus expansion, which supports the necessity of cytokinesis-related transcripts in the final stages of COC maturation. The resulting alterations and abnormalities in oocyte diameter and PB extrusion by RI are due to the direct effect of ROCK on tubulin and other cytoskeleton proteins' organization [31,42,44,[50][51][52][53][54][55][56]. Moreover, ZP thickness decreased with increasing RI supplementation duration.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that spindle organization and polar body extrusion are not coordinated by a single gene. Many cytokinesis-related proteins, including actin, formin, profilin, cofilin, myosin, and tubulin, are effectors of the ROCK signaling pathway though which spindle positioning is regulated [43,[52][53][54][61][62][63][64]. Moreover, ROCK inhibitor increased cellular microtubule acetylation because ROCK regulates microtubule acetylation via phosphorylation of tubulin polymerization-promoting protein 1 [44,50].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we observed the accumulation of excessive cytoplasmic actin mesh around spindles after CAP1 knockdown. The depletion of actin nucleators responsible for the formation of new actin filaments, such as FMN2 (Leader et al, 2002), SPIRE (Pfender et al, 2011) and the ARP2/3 complex (Sun et al, 2011b), or actin-binding proteins responsible for the maintenance of actin filaments, such as capping protein , tropomodulin (Jo et al, 2016), tropomyosin-3 (Jang et al, 2014) or filamin A (Wang et al, 2017) have been shown to impair asymmetric division by decreasing actin networks in oocytes. In contrast, excessive amounts of actin filaments in the cytoplasm have also been shown to be detrimental to spindle migrations, as seen with actin stabilization through GFP-UtrCH overexpression (Holubcová et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Because CAPs enhance the actin-severing activity of cofilin in vitro (Jansen et al, 2014), CAP1 knockdown in oocytes may complement excessive expression of active (S3A mutant) cofilin, which effectively decreases actin levels (Wang et al, 2017). We examined the amount of actin mesh under various conditions: CAP1 knockdown, constitutively active cofilin overexpression, and both CAP1 knockdown and cofilin overexpression.…”
Section: Overexpression Of Full Length Cap1 Decreased Cytoplasmic Actmentioning
confidence: 99%